2015
DOI: 10.1099/vir.0.000172
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen and viruses: a breathing story

Abstract: The effect of oxygen on virus replication is complex, and the role of hypoxia-inducible factor 1a (HIF-1a) in the metabolism of virus-infected cells remains uncertain. Solid tumours are hypoxic, and some viruses use this low oxygen tension level to facilitate their replication in tumour cells, thereby causing cell lysis. In addition, the interactions between viruses and HIF-1a may stimulate a trained immunity. However, the evolutionary basis for the oxygen regulatory mechanism of virus replication is ill-defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…Both were associated with lower than average CD4 + counts during the acute phase. is high viral replication phase [8] has been reported to have complex relationships with oxygen effects [92], which may also suggest the twisted CD4 + count trends in response to the LDH and red blood cell in our data. Aerobic endurance is referred to as the functional state of the oxygen AIDS Research and Treatment transport system [93] and has been reported to be reduced in HIV positive patients than negative ones [94][95][96].…”
Section: Discussionsupporting
confidence: 51%
“…Both were associated with lower than average CD4 + counts during the acute phase. is high viral replication phase [8] has been reported to have complex relationships with oxygen effects [92], which may also suggest the twisted CD4 + count trends in response to the LDH and red blood cell in our data. Aerobic endurance is referred to as the functional state of the oxygen AIDS Research and Treatment transport system [93] and has been reported to be reduced in HIV positive patients than negative ones [94][95][96].…”
Section: Discussionsupporting
confidence: 51%
“…pB19-M20 replicated and produced infectious virions in B19V-semipermissive UT7/Epo-S1 cells (29) as well as in human embryonic kidney 293 (HEK293) cells when an adenoviral helper plasmid that expresses the adenoviral E2, E4orf6, and VA genes was provided (52,53). The production of infectious progeny virions from pB19-M20-transfected UT7/Epo-S1 cells was significantly improved when cells were cultured under hypoxia (1% O 2 ) (54), as hypoxia has been shown to enhance B19V replication (55,56). Several full-length genomes of B19V have been sequenced FIG 1 B19V transcription map.…”
Section: B19v Genome Organization and Expressionmentioning
confidence: 99%
“…18 Influenza viruses are among viruses that oxygen dependent for growth and replication. 19 The chronic hypoxia state and polycythemia in patients with CHD-associated PAH and Eisenmenger syndrome may inhibit virus replication. However, the behavior of SARS-CoV2 with reduced oxygen environments in CHD-associated PAH and severe PAH is unknown.…”
Section: The Chronic Hypoxia Statementioning
confidence: 99%